Tailored Centrifugal Turbomachinery for Electric Fuel Cell Turbocharger - Dietmar Filsinger; Gen Kuwata; Nobuyuki Ikeya (International Journal of Rotating Machinery)
Hydrogen fuel cell technology is identified as one option for allowing efficient vehicular propulsion with the least environmental impact on the path to a carbon-free society. Since more than 20 years, IHI is providing charging systems for stationary fuel cell applications and since 2004 for mobile fuel cell applications. The power density of fuel cells substantially increases if the system is pressurized. However, contaminants from fuel cell system components like structural materials, lubricants, adhesives, sealants, and hoses have been shown to affect the performance and durability of fuel cells. Therefore, the charging system that increases the pressure and the power density of the stacks inevitably needs to be oil-free. For this reason, gas bearings are applied to support the rotor of a fuel cell turbocharger. It furthermore comprises a turbine, a compressor, and, on the same shaft, an electric motor. The turbine utilizes the exhaust energy of the stack to support the compressor and hence lower the required electric power of the air supply system. The presented paper provides an overview of the fuel cell turbocharger technology. Detailed performance investigations show that a single-stage compressor with turbine is more efficient compared to a two-stage compressor system with intercooler. The turbine can provide more than 30% of the required compressor power. Hence, it substantially increases the system efficiency. It is also shown that a fixed geometry turbine design is appropriate for most applications. The compressor is of a low specific speed type with a vaneless diffuser. It is optimized for operating conditions of fuel cell systems, which typically require pressure ratios in the range of 3.0.